Cooperative Collection Management in the Humanities in the Netherlands - Voorbij, Henk (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
In 1998 a project was started in the Netherlands, which aimed to increase the coverage of specialised publications in the humanities. Seven academic libraries participate in the project. The project has been made possible by financial support from the Netherlands Organisation for Scientific Research. The article is built up in four paragraphs: 1. The background to the project. 2. A brief description of its main purposes. 3. The results of an intermediate evaluation, which took place in 2004. 4. The immediate future of the project and reviews the factors that have made it successful.